The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations A SEPARATE DRAWER FOR UNDERCLOTHING Underclothes should be stored away from day-clothes. They should be washed as often as possible. At night they should be hung out to air instead of being folded. SOAP THE SEAMS If you suspect that heavy articles of clothing — greatcoats, men's suits, etc. — may have picked up vermin of some sort, it is a good plan to soap the scams, inside, of course, and then iron through a damp cloth on the outside. Read the section on vermin carefully, DUST IS DANGEROUS, EVEN IN CLOTHES Heavy winter garments cannot, of course, be washed like light summer wear, but a run-over with the electric vacuum cleaner, if you own one, or a very thorough shaking in the open air and a good brushing, will help to remove the dust particles. [illustration] Get rid of dust. CHANGE YOUR STOCKINGS Socks and stockings should be changed frequently and washed as soon as possible. Darn when they are clean, before wearing. Silk and other thin stockings should be washed each time they are worn, as this greatly strengthens them and lengthens their life. Give the children bedroom slippers, home-made if necessary, and do not let them run about in stocking-feet. Both for health and for comfort it is wise to change socks or stockings after muddy games and after a long hike. Children often have to be reminded of this health rule. It is easy in modern homes with adequate hot water to rub through socks and stockings in the bathroom. [illustration] Wash socks and stockings often. 16 177/5/8/2